Transient Aortic Occlusion Augments Collateral Blood Flow and Reduces Mortality During Severe Ischemia due to Proximal Middle Cerebral Artery Occlusion - Ramakrishnan, Gomathi (Transl Stroke Res, 2015)
Cerebral collateral circulation provides alternative vascular routes for blood to reach ischemic tissues during stroke. Collateral therapeutics attempt to augment flow through these collateral channels to reduce ischemia and brain damage during acute ischemic stroke. Transient aortic occlusion (TAO) has pre-clinical data suggesting that it can augment collateral blood flow and clinical data suggesting a benefit for patients with moderate cortical strokes. By diverting blood from the periphery towards the cerebral circulation, TAO has the potential to augment primary collateral flow at the circle of Willis and thereby improve outcome even during large, hemispheric strokes. Using proximal middle and anterior cerebral artery occlusion in rats, we demonstrate that TAO reduces mortality and improves collateral blood flow in severely ischemic animals. As such, TAO may be an effective therapy to reduce early mortality during severe ischemia associated with proximal occlusions.